The new approach of the production technique of discontinuous Cu-C composite - Rudolf, Rebeka; Anžel, Ivan (Anali PAZU, 2022)
The samples of the Cu-C composite were produced by two different techniques: (i) the sintering of powders, and (ii) the internal carbonisation of rapidly solidified pure copper. The aim of the present research was to produce a discontinuous Cu-C composite with the submicron dispersion of graphite particles. The results of our microstructural investigation show that the use of the mechanical alloying and sintering of consolidated powders is an inappropriate way to achieve a submicron dispersion of the graphite particles. On the other hand, the combination of rapid solidification and internal carbonisation was found to be an efficient technique to obtain the requested microstructure.